BUILDING THE BEST FINANCIAL PLANNING TO PROVIDE OPTIMAL PROFIT AT PT ESA DANA UNGGUL - Eli Susiani Br Ginting; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Dimas Angga Negoro (Jurnal Scientia, 2023)
In running their business, property developers often have difficulty for obtaining fast funds for their capital needs. On the other side, investors tend to like many choices /various types of investment instruments that offer high returns and investment security. PT Esa Dana Unggul (EsaDana) is builded a company that meets the needs and wants of every consumer in investment needs through the Securities Crowd Funding platform. As a provider, Esa Dana offers credible product and service analysis so as to minimize the risk of loss for the investors. By making the best financial planning, the company’s finance will be allocated to create all interests that can have benefits within the company line. Starting from Cash Flow Projections, Capital Requirements, Financial Report Projections, Investment Feasibility Ratios and Company Financial Ratios that has been prepared using the best scheme, it is predicted that Esa Dana will be able o generate profits according to the expected time and value. Based on the analysis in this research, PT Esa Dana Unggul implements a differentiation strategy. PT Esa Dana strives to create superior value for customers compared to competitors in the securities crowd funding industry. Financial planning elements depart from the four main functions of company activities, namely the Marketing, Operational, Human Resources and Risk Management functions. These four functions will require costs to run business. These costs can be collected in each function and will later be taken into account in the company’s financial planning and company bookkeeping which will be used by our own management to determine the company’s running steps will influence the company’s strategy.